Strategies of Qur’an–Hadith Teachers in Enhancing Students’ Interest in Reading the Qur’an at State Islamic Senior High School 1 Sarolangun - Abdullah Yunus; Sumirah; Rahmi Apriani (The Islamic Education and Multiculturalism Foundation, 2026)
Abstrak Penelitian ini membahas strategi guru Al-Qur’an Hadis dalam meningkatkan minat membaca Al-Qur’an di kalangan siswa kelas VIII Madrasah Aliyah Negeri 1 Sarolangun. Latar belakang penelitian ini berangkat dari fenomena rendahnya minat baca Al-Qur’an secara mandiri di kalangan remaja madrasah, meskipun secara institusional sudah banyak program keagamaan yang diterapkan. Tujuan penelitian adalah menganalisis efektivitas berbagai strategi pembelajaran dan solusi yang digunakan guru serta kontribusi lingkungan sekolah dan keluarga dalam membangun budaya literasi Qurani. Metode penelitian menggunakan pendekatan kualitatif fenomenologis dengan teknik observasi, wawancara mendalam, dan dokumentasi. Hasil penelitian menunjukkan bahwa minat baca siswa cenderung tumbuh seiring rutinitas, motivasi, keteladanan guru, dan dukungan keluarga serta budaya madrasah. Strategi pembiasaan, penghargaan, pendekatan kontekstual, kegiatan keagamaan, dan kolaborasi dengan orang tua menjadi faktor dominan. Namun, masih ditemukan kendala pada motivasi intrinsik siswa serta pengaruh media sosial yang memerlukan solusi berkelanjutan. Penelitian ini menegaskan pentingnya sinergi guru, madrasah, dan keluarga dalam menciptakan generasi Qurani yang adaptif di era modern. Kata Kunci: Minat membaca Al-Qur’an, strategi guru, pembiasaan, motivasi, budaya madrasah, kolaborasi keluarga Abstract This study examines the strategies of Qur’an Hadith teachers in increasing the interest in reading the Qur’an among eighth-grade students at Madrasah Aliyah Negeri 1 Sarolangun. The research is motivated by the low interest in independent Qur’an reading among madrasah adolescents, despite the institution’s implementation of various religious programs. The aim is to analyze the effectiveness of instructional strategies and solutions applied by teachers, as well as the role of school and family environment in building a culture of Qur’anic literacy. A qualitative phenomenological approach with observation, in-depth interviews, and documentation was employed. Results show that students’ reading interest tends to develop through routines, motivation, teacher role modeling, and support from both family and the madrasah culture. Main factors include habitual practice, recognition, contextual learning, religious activities, and collaboration with parents. Barriers remain regarding students’ intrinsic motivation and the influence of social media, highlighting the need for sustainable solutions. The research emphasizes the importance of synergy among teachers, madrasah, and families to foster a Qur’anic generation that is adaptive in the modern era. Keywords: Qur’an reading interest, teacher strategy, habituation, motivation, madrasah culture, family collaboration